2016
DOI: 10.1590/0102-778631320150139
|View full text |Cite
|
Sign up to set email alerts
|

Projeções de Vazão Afluente à Lagoa Mangueira com Base em Cenários de Mudanças Climáticas

Abstract: Resumo Neste trabalho é apresentada a avaliação dos impactos das mudanças climáticas sobre a vazão de contribuição à lagoa Magueira, localizada no sul do Brasil, com base em projeções de precipitação de vinte Modelos Climáticos Globais (MCGs) que alimentam o modelo hidrológico IPH II. As projeções foram baseadas em dois cenários de mudanças climáticas definidos pelo IPCC que estabelecem as forçantes para que os MCGs estimem o clima futuro: A2, caracterizado pelas altas emissões e B2, caracterizado pelas baixas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
4
0
2
Order By: Relevance
“…The presence of trends also was identified in the Juquiá watershed, São Paulo, by Teixeira et al (2020), both increase and decrease in monthly precipitation and minimum and maximum monthly streamflow, as well as growth tendency in minimum monthly streamflow series. In Rio Grande do Sul, changes in the average annual river flow were identified by Tejadas et al (2016), with an increase of 2.86% and 2.48% in scenarios A2 (the most pessimistic) and B2 (intermediate scenario) considering a near horizon, and 16.94% and 11.83% in the long term.…”
Section: Extreme Value Theorymentioning
confidence: 99%
“…The presence of trends also was identified in the Juquiá watershed, São Paulo, by Teixeira et al (2020), both increase and decrease in monthly precipitation and minimum and maximum monthly streamflow, as well as growth tendency in minimum monthly streamflow series. In Rio Grande do Sul, changes in the average annual river flow were identified by Tejadas et al (2016), with an increase of 2.86% and 2.48% in scenarios A2 (the most pessimistic) and B2 (intermediate scenario) considering a near horizon, and 16.94% and 11.83% in the long term.…”
Section: Extreme Value Theorymentioning
confidence: 99%
“…In Rio Grande do Sul, a study by Tejadas et al (2016) identified changes in the average annual river flow with an increase of 2.86% and 2.48% in scenarios A2 (the most pessimistic) and B2 (intermediate scenario) considering a near horizon, and 16.94% and 11.83% considering a long term.…”
Section: Trend Analysismentioning
confidence: 99%
“…As projeções geradas pelo conjunto de MCG são utilizadas para alimentar os modelos hidrológicos de forma a serem calculadas variáveis de interesse a lagos, como as vazões e cargas afluentes. Recentes estudos na América do Sul (e.g., TASSI et al, 2013;BRAVO et al, 2014;SORRIBAS et al, 2016;TEJADAS et al, 2016;BRÊDA et al, 2020) têm utilizado projeções de variáveis climáticas geradas por modelos climáticos globais como dados de entrada a modelos hidrológicos para verificar o impacto nas principais variáveis hidrológicas.…”
Section: Introductionunclassified
“…Tejadas et al (2016) e brevemente apresentada a seguir. Ressaltamos que, no presente trabalho, são utilizados dados do AR5, enquantoTejadas et al (2016) se apoiaram em dados do AR4. nutriente.…”
unclassified